Emergency coronary and peripheral arteries combined with percutaneous intervention in the elderly: success or therapeutic excess?. (September 2015) - Pepe, Martino; Furgieri, Alessandro; Miranda, Marianna; Cafaro, Alessandro; Paradies, Valeria; Iacovelli, Fortunato; Castriota, Fausto; Liso, Armando
Acute lower extremities peripheral artery disease represents a clinical emergency. Peripheral artery disease incidence ranges from 2.5 to 22% and has progressively increased due to the world population aging phenomenon and associates with coronary artery disease with a rate of 40–60%. The authors present the case of an 89-year-old man coming to their attention with acute lower extremities ischemia and unstable angina. Despite the short-to-midterm favorable outcome, doubts remain about the opportunity of treating 'very old' patients. The lack of dedicated randomized trials and of defined guidelines is a problem the scientific community needs to face considering that patients over 85 years represent a raising quote of the whole population of our catheterization laboratories.